GIGANTEA is a nuclear protein involved in phytochrome signaling in Arabidopsis - Huq, Enamul (The National Academy of Sciences, 2000)
In a genetic screen of available T-DNA-mutagenized Arabidopsis populations for loci potentially involved in phytochrome (phy) signaling, we identified a mutant that displayed reduced seedling deetiolation under continuous red light, but little if any change in responsiveness to continuous far-red light. This behavior suggests disruption of phyB, but not phyA signaling. We have cloned the mutant locus by using the T-DNA insertion and found that the disrupted gene is identical to the recently described GIGANTEA (GI) gene identified as being involved in control of flowering time. The encoded GI polypeptide has no sequence similarity to any known proteins in the database. However, by using β−glucuronidase-GI and green fluorescent protein-GI fusion constructs, we have shown that GI is constitutively targeted to the nucleus in transient transfection assays. Optical sectioning by using the green fluorescent protein-GI fusion protein showed green fluorescence throughout the nucleoplasm. Thus, contrary to previous computer-based predictions that GI would be an integral plasmamembrane-localized polypeptide, the data here indicate that it is a nucleoplasmically localized protein. This result is consistent with the proposed role in phyB signaling, given recent evidence that early phy signaling events are nuclear localized.